From Pixels to Prognosis: Artificial Intelligence and Machine Learning Models in Brain Tumour Mutation Prediction - Quratulain Tariq; Eisha Abid Ali; Saad bin Anis; Irfan Yousaf; Ahmer Nasir Baig; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2024)
Brain tumours are a leading cause of death and disability, impacting individuals across all ages, genders, and ethnicities. They are primarily diagnosed using MRI but a precise diagnosis is dependent on the molecular biology of the tumour studied on the pathological specimen. Artificial intelligence and machine learning are forging new paths through diagnostic obstacles, offering the intriguing benefits of non-invasive diagnosis, pattern recognition, and outcome prediction from imaging data. Here, we present a literature review on the role of machine learning in tumour mutations using imaging alone. Keywords: brain tumor, artificial intelligence, machine learning, tumor mutation.